Alzheimer risk genes modulate the relationship between plasma apoE and cortical PiB binding. (October 2015) - Lazaris, Andreas; Hwang, Kristy S.; Goukasian, Naira; Ramirez, Leslie M.; Eastman, Jennifer; Blanken, Anna E.; Teng, Edmond; Gylys, Karen; Cole, Greg; Saykin, Andrew J.; Shaw, Leslie M.; Trojanowski, John Q.; et al.
Abstract : Objective: We investigated the association between apoE protein plasma levels and brain amyloidosis and the effect of the top 10 Alzheimer disease (AD) risk genes on this association. Methods: Our dataset consisted of 18 AD, 52 mild cognitive impairment, and 3 cognitively normal Alzheimer's Disease Neuroimaging Initiative 1 (ADNI1) participants with available [ 11 C]-Pittsburgh compound B (PiB) and peripheral blood protein data. We used cortical pattern matching to study associations between plasma apoE and cortical PiB binding and the effect of carrier status for the top 10 AD risk genes. Results: Low plasma apoE was significantly associated with high PiB SUVR, except in the sensorimotor and entorhinal cortex. For BIN1 rs744373, the association was observed only in minor allele carriers. For CD2AP rs9349407 and CR1 rs3818361, the association was preserved only in minor allele noncarriers. We did not find evidence for modulation by CLU, PICALM, ABCA7, BIN1, and MS4A6A . Conclusions: Our data show that BIN1 rs744373, CD2AP rs9349407, and CR1 rs3818361 genotypes modulate the association between apoE protein plasma levels and brain amyloidosis, implying a potential epigenetic/downstream interaction.